The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4209/aaqr.2017.04.0127
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Diesel/Biodiesel Particulate Exhaust by FTIR Spectroscopy and Mass Spectrometry: Impact of Fuel and Driving Cycle

Abstract: The growing concern about air quality and the impact exhaust particles can have on the environment has resulted in the increased use of alternative fuels. A sampling campaign from a conventional heavy diesel engine operated in typical transient cycle or steady-state condition, and running on diesel, 30% biodiesel in diesel, and 100% biodiesel was carried out. The particulate composition was characterized using Fourier Transform Infrared (FTIR) spectroscopy, Two-step Laser Mass Spectrometry (L2MS), Secondary Io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 83 publications
(102 reference statements)
1
19
0
Order By: Relevance
“…According to the ATR-FTIR analysis, the spectra showed three interesting major signals (Fig. 7) for carbon containing compounds that are emitted from fossil fuel combustion such as traffic tailpipe emissions (e.g., Siciliano et al 2018;Popovicheva et al 2017;Shaltout et al 2016;Agudelo-Castañeda et al 2015;Popovicheva et al 2015;Jiang et al 2011). The first signal (wave number 800-1100 cm −1 ; mass fraction 37.1-45.6%) represents polycyclic aromatic hydrocarbon compounds that contain functional groups such as sulfur, hydroxyl, or ester.…”
Section: Gravimetric and Black Carbon Analysismentioning
confidence: 99%
“…According to the ATR-FTIR analysis, the spectra showed three interesting major signals (Fig. 7) for carbon containing compounds that are emitted from fossil fuel combustion such as traffic tailpipe emissions (e.g., Siciliano et al 2018;Popovicheva et al 2017;Shaltout et al 2016;Agudelo-Castañeda et al 2015;Popovicheva et al 2015;Jiang et al 2011). The first signal (wave number 800-1100 cm −1 ; mass fraction 37.1-45.6%) represents polycyclic aromatic hydrocarbon compounds that contain functional groups such as sulfur, hydroxyl, or ester.…”
Section: Gravimetric and Black Carbon Analysismentioning
confidence: 99%
“…collected the vehicle exhaust samples near the diesel bus terminals in Colorado and found that carbon fraction accounted over 95% in PM 2.5 . Popovicheva et al (2017) tested a heavy diesel engine in different driving conditions using alternative diesel fuels. Cheng et al (2010) measured tunnel and roadside PM emissions of on-road vehicles in Hong Kong during 2003, and calculated emission factor (EF) of diesel and non-dieselfueled vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Organic compounds are defined as all the organic species (aromatic or aliphatic molecules and their fragments) that are detected in the positive polarity spectra. Carbon clusters Cnare considered to be a marker for elemental carbon [49,50,51] and form the second group. All the inorganic species, with the exception of sulphur-bearing compounds, were interpreted as ash (metals).…”
Section: Size-resolved Particle Characterisation (Kinetics™)mentioning
confidence: 99%